Problematika Pengajuan Sertifikasi Halal: Studi Kasus UMKM di Pasar Kordon - Zulaiha, Siti; Saepurohman, Muhammad (Ikatan Da'i Indonesia, 2024)
Indonesia is one of the largest Muslim-majority countries in Southeast Asia. Kordon Market is one of the traditional markets located in Bandung, precisely on Jl. Ibrahim Adjie, Kujangsari, Bandung. Kordon Market is like other traditional markets where there are many traders who sell basic or primary daily necessities. There is a fact that the majority of people around the Kordon market or 97% are Muslims and the remaining 3% of the population are non-Muslims. So, it requires food products that are in accordance with the provisions of Islamic law. The type of research used is a type of field research, namely research with the aim of obtaining data directly into the field and literature study, namely data collection by understanding and studying theories from various literature related to research. Halal certification is a fatwa written by the Indonesian Ulema Council stating that a halal product must be in accordance with Islamic law. The purpose of a halal certificate is to guarantee the halal certainty of a product so that it can calm the hearts of those who consume it.The results of this study indicate that the causes of the large number of SMEs that have not yet been halal certified are Micro, Small and Medium Enterprises who think that halal certification is not something important, because the products they manage use safe basic ingredients so that it has been proven that they are halal because there is no addition or mixture with ingredients or something haram, Lack of knowledge about halal certification, Assume the process of applying for halal certification is not easy or complicated, Have limited funds to obtain halal certificates.